Perilaku Hidup Bersih dan Sehat dan Pengelolaan Sampah Terhadap Kejadian Diare Pada Masyarakat di Wilayah Desa Bantarjaya Kabupaten Bogor - Amalia; Nina (MPI Press, 2022)
Introduction: Until now, diarrhea is still a major problem in society that is difficult to overcome, diarrhea is one of the diseases that causes mortality and malnutrition in children. Factors related to the incidence of diarrhea are inadequate provision of clean water, water contaminated by feces, lack of hygiene facilities, unhygienic disposal of feces, poor personal and environmental hygiene, and improper preparation and storage of food. Objectives: This research aims to determine the relationship between Clean and Healthy Living Behavior (PHBS) and Waste Management on the incidence of diarrhea in the Bantarjaya Village area among the people of Bogor Regency. Methods: This research is a quantitative study with a correlational research design, and uses a cross-sectional approach. Results: There is a relationship between Exclusive Breastfeeding (P= 0.000), Washing Hands with Soap (P = 0.000), Healthy Latrines (P = 0.000) and Waste Management (P = 0.000) but there is no relationship between Clean Water Sources (P = 0.469) and the incidence of Diarrhea. Conclusion: The lack of public knowledge regarding exclusive breastfeeding, washing hands with soap, using healthy latrines, and waste management is also caused by low income so that many people still channel pipes directly into rivers and throw rubbish carelessly, so this is related to the existence of a Life Behavior relationship. Clean and Healthy and Waste Management on Diarrhea Incidents in the Bantarjaya Village Area, Bogor Regency.